EFFECTIVENESS OF HANDWASHING PRACTICE DEMONSTRATION IN CHILDREN AGED 7-9 YEARS AS A PREVENTIVE EFFORT OF DIARRHEA OCCURRENCE AT SON SIDOTENTREM II BANGILAN DISTRICT TUBAN REGENEY IN 2017 - Mulyani, Sri (AKADEMI KESEHATAN RAJEKWESI BOJONEGORO, 2019)
ABSTRACT Health education is an effort or activity to create behavior of society which is conducive to health. Less clean hand wash in children is one factor that can cause diarrhea. The purpose of this study is to know the effectiveness of handwashing practice demonstration in children aged 7-9 years as a preventive effortof diarrhea occurrence at SDN Sidotentrem II Bangilan District Regeney Tuban in 2017.The type of research used is experimental research, research design using quasi pra eksperimen (pre-post test design). The population is all children aged 7-9 years, 140 children, and the number of samples are 140 respondents who meet the inclusion criteria by using non probability sampling with saturated sampling technique. Methods of data collection with handwashing demonstration questionnaire which then in editing, coding, scoring and tabulating, are presented in the estimation and percentage curve tables.The result of the research showed that from /40 respondents before getting handwashing demonstration, the majority was not correct in hand washing as many as 140 respondents (100%). respondents after hand washing demonstration from 140 respondents more than partially true in hand washing practice as many as 94 respondents (67./%) and less than partially incorrect in hand washing practice as many as 46 respondents (32.9%).In conclusion effective handwashing demonstration in children aged 7-9 years as apreventive effort incident diarrhea in SDN Sidotentrem II District Bangilan Tuban Regeney. The results of this study are expected to add knowledge and skills to the respondents about the practice of hand washing correctly. Keywords: Handwashing Practice, Demonstration.